Poster 253: Anterior Cruciate Ligament Reconstruction in 118 Competitive Wrestlers: Outcomes, Reoperations, and Return to Play at 5 years Mean Follow Up. Issue 7 (30th July 2022) - Song, Bryant; Wasserburger, Jory; Till, Sara; Camp, Christopher; Levy, Bruce; Stuart, Michael; Okoroha, Kelechi; Krych, Aaron; Marigi, Erick
Objectives:Introduction: Wrestling is a physically demanding sport with young athletes prone to anterior cruciate ligament (ACL) injuries. However, there is a paucity of data evaluating the results of ACL reconstruction (ACLR) in this cohort. Purpose: To assess patient-reported outcomes, reoperation rates, graft survival, and return to play (RTP) following ACLR in a large cohort of competitive wrestlers Methods: All competitive wrestlers (high school, collegiate, or professional) with a history of an ACLR at a single institution between 2000 and 2019 were retrospectively identified. Graft failure was defined as a re-tear determined by clinical or advanced imaging evaluation, and/or revision ACL reconstruction. All patients were contacted for determination of reinjury rates, current sport status, visual analog scale (VAS), International Knee Documentation Committee (IKDC) and Tegner activity scores. Results: 118 knees in 114 wrestlers were included at a median follow-up time of 5.8 years (IQR: 3.6 – 10.3). The median age was 17 years (15 – 18) with 116 (98%) males. ACLR was most often performed with bone-patellar tendon-bone (BTB) autograft (n = 64; 54%) or hamstring tendon (HT) autograft (n = 43; 36%). At final follow-up, 80% of athletes were able to RTP at a median of 273 days (IQR: 203 – 379). Graft failure occurred in 17 (14%) patients at a median time of 1.4 years (IQR: 0.8 – 4.7) after the index ACLR. BTB autograft demonstrated a lower failure rate compared to HT autograft (8% vs. 21%; P = 0.044). Kaplan-Meier survivorship free from graft failure for the entire cohort was 95.3% at 1 year, 92.5% at 2 years, 89.8% at 5 years, 84.6 at 10 years, 77.6 at 20 years. BTB autograft was associated with better survival than HT autograft up to 15 years after the index ACLR (90.4% vs. 76.3%; P = 0.030). Conclusions: Return to competitive wrestling was observed in 80% of athletes after ACLR, with 14% of wrestlers experiencing graft failure. BTB autograft reconstruction may serve as a more durable graft for competitive wrestlers with lower rates of failure when compared to HT autograft even up to 15 years after surgery. Table 1. Baseline Demographic, Clinical, and Operative Data Figure 1. Kaplan-Meier survivorship curve demonstrating progression to graft failure of the entire cohort. Figure 2. Kaplan-Meier curve demonstrating progression to graft failure of each graft type. Figure 3. Kaplan-Meier curve demonstrating progression to graft failure of BTB autograft vs. hamstring autograft